An integrated dynamic model for the volcanic activity at Poas volcano, Costa Rica - Casertano, L. (1987)
A dynamic model for the activity of Poas Volcano, Costa Rica, is proposed. Data collected during a three-year period show that the volcanic processes occur within a small hydrothermal system. Heat is supplied by a magma body in the conduit and is transferred to the surface by fluid convection. Within a given volume of rock, pore pressure builds up due to the upward motion of fluids and the increase in vapor pressure when the temperature rises above the boiling point. Ultimately, the system becomes unstable when the pore pressure overcomes the total pressure. This leads to the assumption that the kinetic and thermal energies are proportional to the depth at which the mechanical equilibrium is disturbed. Laboratory experiments were performed by heating samples of the crater lake deposits. The preliminary results of these experiments show significant analogies with the low-energy activity of the volcano. Following this model we estimated that a phreatic explosion which reaches 200 m in height (comparable to the one observed by Francis et al. in 1978) originates at a depth of 70 m and a temperature of 180 ° C; these values agree with those reported in the literature. In addition, "magmatic" sulfur, which partitions into the rising hydrothermal fluids, reacts at lower temperature and higher _t"O2 to produce pockets of liquid sulfur in the conduit deposits and the lava dome. These pockets are subsequently erupted forming the pyroclastic sulfur.